2018
DOI: 10.1016/j.marenvres.2018.05.017
|View full text |Cite
|
Sign up to set email alerts
|

The effects of elevated CO2 on shell properties and susceptibility to predation in mussels Mytilus edulis

Abstract: For many species, ocean acidification (OA) is having negative physiological consequences on their fitness and resilience to environmental change, but less is known about the ecosystem effects of these changes. Here, we assess how OA conditions predicted for 2100 affects the biological functioning of an important habitat-forming species Mytilus edulis and its susceptibility to predation by a key predator, the gastropod Nucella lapillus. Change in three physiological parameters in Mytilus were assessed: (1) shel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 80 publications
0
22
0
Order By: Relevance
“…2014 a – b ,; Sadler et al . ). However, field studies along latitudinal gradients in temperature and CaCO 3 saturation state suggest that patterns in shell thickness are taxon‐specific.…”
Section: Discussionmentioning
confidence: 97%
“…2014 a – b ,; Sadler et al . ). However, field studies along latitudinal gradients in temperature and CaCO 3 saturation state suggest that patterns in shell thickness are taxon‐specific.…”
Section: Discussionmentioning
confidence: 97%
“…Perkol-Finkel and Sella (2014) demonstrated that reducing alkalinity by the use of different composites in the concrete could increase percentage live cover and enhance the recruitment of ecosystem engineers. Conversely, increasing acidity has also been shown to change 'perception' of chemical cues, significantly altering predator-prey dynamics in larval fish (Dixson et al 2010) and bivalves (Sadler et al 2018), and the recruitment of meiofauna (Lee et al 2017). Oyster settlement can be induced by the glycyl-glycly-L-arginine (GGR) protein, produced within the shell (Crisp 1967), but it is only effective once larvae are within close proximity (cm-mm) of the surface bound cue (Browne and Zimmer 2001).…”
Section: Discussionmentioning
confidence: 99%
“…At current CO 2 emission rates, by 2100 atmospheric CO 2 concentrations are predicted to exceed 1000 ppm in some instances (Stocker et al, 2013), leading to reductions in pH of between 0.3 and 0.4 units from today's conditions (Doney et al, 2009). For marine life, changes in pH can have significant, detrimental effects on their structure and functioning (Lemasson et al, 2017a(Lemasson et al, , 2018 including abnormal larval development (Kurihara et al, 2007;Kurihara, 2008), increased pressure on acid-base regulatory mechanisms (Lindinger et al, 1984;Thomsen and Melzner, 2010;Scanes et al, 2017) and changes to behavior (Queiros et al, 2015;Sadler et al, 2018). For calcifying species, OA can be especially problematic due to disruption of the biomineralization process that is so crucial to the development of shells, exoskeletons and tests.…”
Section: Introductionmentioning
confidence: 99%
“…Under normal conditions, these crystals are arranged as horizontal sheets (Checa et al, 2006;Hahn et al, 2012) but under predicted future climate conditions, crystal formation can become disordered and the crystals themselves misorientated or porous (Hahn et al, 2012;Fitzer et al, 2014a,b;Li et al, 2015;Meng et al, 2019; Figure 1). It is argued that these changes will have negative consequences for shell integrity and material properties (e.g., Beniash et al, 2010;Fitzer et al, 2015b), impacting the potential for mollusks to withstand physical and biological stress (Sadler et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation